Requirements on Management Practices for the Development of Entrepreneurial Creativity in a Global Social-ecological System – Case Study. (2015) - Tripon, Avram
Abstract: We follow a general framework for analysing the sustainability of socio-ecological systems – with a strong human intervention, for Entrepreneurial creativity in a global social-ecological system. In order to define the economic and socio-cultural contextual factors that facilitate or hinder the development of creative skills we applied questionnaires to entrepreneurs, managers and staff of 10 enterprises. We can say that the main problem managers see with their enterprises is a source of financing, while employees feel that there are organizational problems. The enterprises are focused on local and regional markets. Managers feel in general they encourage creative solutions to problems, creative individual contributions by employees; employees rarely downsize these managerial approaches. Both managers and employees feel in general that they work on challenging and important projects and that their work is at the very least productive. Managers often think they are a good example for their employees and workers tend to think the same way. Both Managers and employees have, for the most part, positive opinions on group work, its dynamics, its effectiveness and validity and on interpersonal relationships present in the work group. In the focus group, managers and employees have similar feelings towards most of the questions raised. Participants creative solutions available. With these solutions start always.